Model of multimedia textbook based on capturing of lectures and aligned with cognitive learning theories : : doktorski rad - Pale, Predrag (P. Pale ; Fakultet elektrotehnike i računarstva, 2014)
ABSTRACT: Lectures still are and will remain the major teaching method in many formal and informal settings. However, according to cognitive learning theories, lectures as a teaching tool have a number of intrinsic deficiencies independent of the teacher or the topic. They are rooted in limited time, necessity for synchronous presence irrespective of student's and teacher's current ability and differences of students' previous knowledge and competencies in general. These deficiencies can be compensated with lecture captures enriched with additional content like: lecturer’s notes, links to prerequisite knowledge, quizzes, FAQ and other web based content. The proposed taxonomy of the rich lecture capture content serves as the foundation for creation of a digital textbook model based on rich lecture captures. Model also defines the rules for contextually synchronous presentation of all content elements as well as for discrete, continuous and indexed navigation in order to reduce cognitive load. The model was verified by developing two different software tools using different languages, tools and platforms. Architecture for publishing digital textbook is proposed enabling distributed publication of textbook’s elements allowing for open or restricted access, on-line or off-line usage and preservation of intellectual property rights. The architecture and model allow for a posteriori amendment and modification of the textbook’s content thus adjusting the textbook for a variety of users, needs and applications thereby extending textbook’s lifetime and reducing its unit production and usage cost. The hypothesis that rich lecture capture could yield better learning outcomes than previously known lecture captures was tested in real life situations and in the laboratory. Although validation shows improvements, they could not be proven to be statistically significant, one reason being rooted in reduced motivation of students to achieve good results on the final exam. Further research is proposed in directions of model validation in various educational settings with variety of designed learning outcomes and in direction of modifying the model for use during live lectures. -